(untitled) (Research, Society and Development, 2021)
A better understanding of the use of biochar with Trichoderma spp. (TRI), considered the most studied tool for biological control, would increase our ability to set priorities. However, no studies exist using the two inputs on plant disease management. Here, we hypothesized that biochar and TRI would be used for the management of soilborne plant pathogens, mainly due to changes in soil properties and its interactions. To test this hypothesis, this review assesses papers that used biochar and TRI against plant diseases and we summarize the handling mechanisms for each input. Biochar acts by mechanisms: induction to plant resistance, sorption of allelopathic and fungitoxic compounds, increase of beneficial microorganisms, changes the soil properties that promote health and nutrient availability. Trichoderma as biocontrol agents by different mechanisms: mycoparasitism, enzyme and secondary metabolic production, plant promoter agent, natural decomposition agent, and biological agent of bioremediation. Overall, our findings expand our knowledge about the reuse of wastes transformed in biochar combined with Trichoderma has potential perspective to formulate products as alternative management tool of plant disease caused by soilborne fungal pathogen and add important information that can be suitable for development of strategy for use in the global health concept.